Predicting the strength of a plastic waste reinforced clay-sand soil mixture using BPNN approach - Senussi, Galal; K. Abdullah, Thikra; S. Omar, Sundus (International Journal of Engineering Research, 2024)
The study aimed to improve soil engineering properties by incorporating waste plastic bottle strips into the soil to enhance its strength. Plastic sheets of varying sizes an percentage were used, and a Back Propagation Neural Network (BPNN) was employed to predict unconfined compressive force. The model accuracy was confirmed by calculating mean absolute errors (MAE) of 0.00336, 0.0491, 0.0344, and 0.0461, indicating its reliability.